Dynamics of Southern Hemisphere Atmospheric Circulation Response to Anthropogenic Aerosol Forcing. Issue 19 (2nd October 2020) - Wang, Hai; Xie, Shang‐Ping; Zheng, Xiao‐Tong; Kosaka, Yu; Xu, Yangyang; Geng, Yu‐Fan
Abstract: Anthropogenic aerosols, concentrated largely in the Northern Hemisphere, not only affect the local climate but also induce pronounced changes in atmospheric circulation that extend into the Southern Hemisphere (SH). In coupled historical single‐forcing simulations, aerosol forcing induces a deceleration of both the subpolar jet (SPJ) and the subtropical jet (STJ) in SH in austral winter. Atmospheric general circulation model experiments indicate that the STJ is weakened by an interhemisphere gradient in the zonal mean sea surface temperature (SST) and an anomalous cross‐equatorial Hadley circulation, while the SPJ response shares similar feedbacks with the greenhouse gas forcing. Specifically, atmospheric eddy adjustments are important for the SPJ change. The atmospheric response unique to anthropogenic aerosol forcing (e.g., cross‐equatorial Hadley cell and the weakened SH STJ) can be exploited for climate change attribution. Plain Language Summary: Anthropogenic increase in aerosol concentrations in the Northern Hemisphere caused not only severe local air pollution but also atmospheric circulation changes as far away as in the Southern Hemisphere. Climatologically, the Southern Hemisphere westerlies show significant seasonal variation; the subtropical jet dominates the upper troposphere during austral winter but diminishes in austral summer. In contrast, the subpolar jet is zonally symmetric and strong in austral summer, but it weakens and exists only over the South Pacific in austral winter. The present study examines austral winter Southern Hemisphere subpolar and subtropical jet responses to historical aerosol forcing over the past century in climate model simulations. Results show that the subpolar and subtropical jets both weaken with little shift in latitudinal position. By reflecting the solar irradiation, the aerosols reduce the sea surface temperature more in the Northern than the Southern Hemisphere. We demonstrate that the hemispheric contrast in the sea surface temperature change induces an anomalous interhemispheric overturning circulation that slows the subtropical jet. Greenhouse gas forcing also influences the Southern Hemisphere westerlies, but with distinct spatial patterns and mechanisms compared to anthropogenic aerosols. Key Points: The Southern Hemisphere atmospheric circulation change is identified in response to anthropogenic aerosol forcing The aerosol forcing weakens the subtropical jet and strengthens the subpolar jet due to the interhemisphere asymmetric SST response The spatially uniform cooling effect of aerosols induces a subpolar and subtropical jet change similar to the GHG effect with sign reversed